Association Between Sleep and Productivity Loss Among 598 676 Employees From Multiple Industries. Issue 4 (May 2018) - Gingerich, Stefan B.; Seaverson, Erin L. D.; Anderson, David R.
Purpose: To examine the relationship between sleep habits and employee productivity. Design: Cross-sectional health risk assessment analysis. Setting: Employer-sponsored health and well-being programs. Participants: A total of 598 676 employed adults from multiple industries. Measures: Self-reported average hours of sleep, fatigue, absence days, and presenteeism. Analysis: Bivariate analyses to assess the relationships between self-reported hours of sleep and self-reported fatigue and mean and median absence and presenteeism. Results: The relationship between sleep hours and both measures of productivity was U-shaped, with the least productivity loss among employees who reported 8 hours of sleep. More daytime fatigue correlated with more absence and presenteeism. Median absence and presenteeism was consistently lower than mean absence and presenteeism, respectively, for the various hours of sleep and levels of fatigue. Conclusion: Organizations looking to expand the value of their investment in employee health and well-being should consider addressing the employee sleep habits that may be negatively impacting productivity.